2010
DOI: 10.1007/s00018-010-0460-1
|View full text |Cite
|
Sign up to set email alerts
|

RhoA/Rho-kinase and vascular diseases: what is the link?

Abstract: RhoA/Rho-kinase pathway plays an important role in many pathological conditions. RhoA participates in the regulation of smooth muscle tone and activates many downstream kinases. The best characterized are the serine/threonine kinase isoforms (Rho-kinase or ROCK), ROCKα/ ROCK2 and ROCKβ/ROCK1. ROCK is necessary for diverse functions such as local blood flow, arterial/pulmonary blood pressure, airway resistance and intestinal peristalsis. ROCK activation permits actin/myosin interactions and smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
137
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 170 publications
(208 reference statements)
3
137
0
6
Order By: Relevance
“…33 Increased RhoA/ROCK activity has been demonstrated in human and experimental hypertension. 34 Antagonizing ROCK using fasudil lowers blood pressure in hypertensive patients. 35,36 Mustafa et al 9 reported that TRPM8-induced gastric fundus contraction is associated with the RhoA/ROCK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…33 Increased RhoA/ROCK activity has been demonstrated in human and experimental hypertension. 34 Antagonizing ROCK using fasudil lowers blood pressure in hypertensive patients. 35,36 Mustafa et al 9 reported that TRPM8-induced gastric fundus contraction is associated with the RhoA/ROCK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of active myosin phosphatase, myosin light chain remains in the phosphorylated and pro-constrictive state. 16 To investigate the potential role that ROCK may play in the increased ET-1 constrictions after OSA, we pretreated isolated PCAs with the nonspecific ROCK1/2 isoform antagonist Y27632 (1 μmol/L; IC 50 = 140 and 300 nmol/L for ROCK1 and ROCK2, respectively). 17,18 In the presence of Y27632, the constrictor responses to IRL-1620 were abolished in denuded PCAs from OSA rats ( Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Activation of ROCK phosphorylates and inactivates the myosin binding subunit of myosin phosphatase (MYPT1), suppresses myosin phosphatase mediated dephosphorylation of myosin light chain, and enhances vasoconstriction. 16 After pretreatment of vessels with the ROCK inhibitor, Y27632, the increased constriction of OSA PCAs was abolished ( Figure 6A). Furthermore, the ratio of phospho-MYPT1 to total MYPT1 was significantly increased in OSA PCAs ( Figure 6B).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Rho-associated serine/threonine kinase family, of which ROCK1 is a member, operates as a key regulator of actin cytoskeleton dynamics and organization (24). ROCK1 has various different roles, including involvement in invasion, metastasis and migration during tumorigenesis (25).…”
Section: Discussionmentioning
confidence: 99%